Photoluminescence property of Ba(Zr0.25Ti0.75)O-3 powders prepared by solid state reaction and polymeric precursor method - Rout, S. K.; Cavalcante, L. S. [UNESP]; Sczancoski, J. C. [UNESP]; Badapanda, T.; Panigrahi, S.; Li, M. Siu; Longo, Elson [UNESP] (Elsevier B.V., 2009)
Ba(Zr0.25Ti0.75)O-3 (BZT) powders were synthesized by the polymeric precursor method (PPM) at different temperatures (400, 500 and 700 degrees C) for 2 h and by the solid state reaction (SSR) at 1350 degrees C for 4 h. These powders were analyzed by X-ray diffraction (XRD), ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns indicated that the crystalline BZT powders prepared by both methods present a cubic structure. The different optical band gap values were observed from the UV-vis spectra, suggesting the presence of intermediary energy levels (shallow and deep holes) within the band gap. When excited with 350 nm wavelength at room temperature, the BZT powders obtained by SSR exhibited only one broad PL band with a maximum at around 467 nm (blue emission). on the other hand, it was noted the presence of two broad bands when BZT powders were prepared by the PPM, where the correspondent positions are influenced by the heat treatment temperatures. Finally, a model was proposed in order to explain the origin of the PL property in these powders. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Crystal structure; Localized states; Photoluminescence